Analysis of Shutdown Testing Maintenance Results Using Omicron CMC 356 Test Equipment on 150 kV Jantho Distance Bay Line Relay in Gi Sigli - Agustina, Gita; anisah, siti; Sastra P Tarigan, Adi (Universitas Medan Area, 2025)
The results of this study aim to analyze shutdown testing using the Omicron CMC 356 test tool on the relay distance in the 150 kV Jantho bay line. Testing was carried out using the Test Advance Distance module to test the time characteristics and the State Sequencer module to simulate the automatic fault and trip functions on the PMT (Circuit Breaker). The test results show that the time characteristics for Zone 1, Zone 2, and Zone 3 are still in accordance with the SPLN T5.002:2021 standard with an error below the tolerance limit of ±5%. In the ground phase fault simulation (R-N), the measured secondary current was 13.67 A with an angle of -72.55°, which is close to the test tool injection result of 13.2 A with an angle of -72.27°. The LED indication on the relay shows a response according to the fault simulation, and the PMT successfully carries out the trip and reclose functions according to the set parameters. This study confirms that the results of maintenance and testing using the Omicron CMC 356 are effective in evaluating the performance of the relay distance and ensuring compliance with applicable standard parameters